2013
DOI: 10.13103/jfhs.2013.28.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Models to Predict Staphylococcus aureus Growth on Processed Cheeses

Abstract: This study developed predictive models for the kinetic behavior of Staphylococcus aureus on pro-cessed cheeses. Mozzarella slice cheese and cheddar slice cheese were inoculated with 0.1 ml of a S. aureus strain mixture (ATCC13565, ATCC14458, ATCC23235, ATCC27664, and NCCP10826). The inoculated samples were then stored at 4 o C (1440 h), 15 o C (288 h), 25 o C (72 h), and 30 o C (48 h), and the growth of all bacteria and of S. aureus were enumerated on tryptic soy agar and mannitol salt agar, respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…The minimum growth temperatures of S. aureus in grilled eggs, peeled quail eggs, and whole egg liquid were estimated to be 3.3, 4.5, and 5.2 °C, respectively. This result was similar to that of a growth prediction model for S. aureus in processed cheese that uses the square root (mozzarella: 6.3 °C, cheddar: 5.7 °C) (Kim et al, 2013). Also, the results of the growth prediction model for S. aureus in dried herring, which uses the square root, showed that the minimum growth temperature about 10 °C, indicating that bacterial growth was different depending on the food (Kang et al, 2013).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The minimum growth temperatures of S. aureus in grilled eggs, peeled quail eggs, and whole egg liquid were estimated to be 3.3, 4.5, and 5.2 °C, respectively. This result was similar to that of a growth prediction model for S. aureus in processed cheese that uses the square root (mozzarella: 6.3 °C, cheddar: 5.7 °C) (Kim et al, 2013). Also, the results of the growth prediction model for S. aureus in dried herring, which uses the square root, showed that the minimum growth temperature about 10 °C, indicating that bacterial growth was different depending on the food (Kang et al, 2013).…”
Section: Resultssupporting
confidence: 80%
“…Similar results were obtained when compared to other studies (Cho et al, 2011b) on the growth prediction model of L. monocytogenes in smoked salmon (A f : 1.03-1.58, B f : 1.01-1.55), a study (Kang et al, 2010) on the growth prediction of S. aureus and Bacillus cereus in RTE foods (A f : 1.04-1.37, Bf: 0.90-1.11), the growth prediction model (Park et al, 2009) of S. aureus in green-bean sprouts provided in school meals (A f : 1.10-1.31, Bf: 0.97-1.03, MSE: 0.002-0.02), and the suitability verification value (Yun et al, 2013) of the growth prediction model for pathogenic E. coli in paprika (A f : 1.04-1.18, B f : 0.98-1.00, MRE: -1.03, -0.04). RMSE for the growth prediction model for grilled eggs, peeled quail eggs, and the whole egg liquid was 0.16, 0.26, and 0.27, respectively, showing a value that is closer to 0 than 0.300-0.5344, the RSME value measured in the study (Kim et al, 2013) on the prediction of growth of S. aureus in cheese. It is similar to the RMSE value of 0.09-0.24 in the predictive model (Park et al, 2010) of S. aureus growth in boiled meat, showing a high suitability.…”
Section: Resultsmentioning
confidence: 61%
“…According to Table 1, the lag phase of S. aureus at 26 °C showed the highest value (4.80 ± 0.07), inversely proportional to ISSN (print) temperature, with the highest μmax at 35 °C (1.05 ± 0.03). These findings are similar to those in previous reports, which showed that the maximum growth rate increased proportionally to the increase in the temperature (Kim et al, 2013;Mansur et al, 2016;Choi et al, 2018). The term of "h0" is a parameter of the Baranyi model that attempts to consider the physiological status of bacteria during growth (Baranyi and Roberts, 1994).…”
Section: Primary Modelsupporting
confidence: 90%
“…For Mozzarella ( A w =0·970) and Cheddar cheeses ( A w =0·965), T min values were 6·35, and 5·72, respectively (Kim et al 2013). Because the T min values from the study by Kim et al (2013) were estimated only at high A w , the T min values were lower than that of our study. These results were impacted by the kinetic behaviour of pathogens, which depends on the food matrix (Yoon, 2010).…”
Section: Resultsmentioning
confidence: 99%